Pengaruh Tingkat Pendidikan, Pendapatan Orang Tua, Dan Lingkungan Belajar Terhadap Hasil Belajar IPS Siswa - Sabriati, Sabriati (Universitas Negeri Makassar, 2018)
. The study aims at examining: (1) The influence of parents’education level on students’ learning results inSocial Sciences atSMP Nusantara Makassar. (2) The influence of parents’income level on students’ learning results in Social Sciences atSMP Nusantara Makassar. (3) The influence of learning environment on students’ learning results in Social Sciences at SMP Nusantara Makassar. (4) The influence of education level, parents’ income, and learning environment simultaneously on students’ learning results in Social Sciencesat SMP Nusantara Makassar. The study is quantitative research with Ex-Post Facto with the total samples of 45 students. Data were collectedby employing questionnaire and documentation. Data were analyzed by employing statistics descriptive analysis and statistics inferential analysis. The results of the study reveal that: (1) There is positive influence of parents’ education level on students’ learning results in Social Sciences at SMP Nusantara Makassar. (2) There is no influence of parents’ income level on students’ learning results in Social Sciences at SMP Nusantara Makassar (3) There is positive influence of learning environment on students’ learning results in Social Sciences at SMP Nusantara Makassar. (4) There ispositive influence of education level, of parents’ income level and learning environment simultaneously on students’ learning results in Social Sciences at SMP Nusantara Makassar.